Stress hyperglycemia ratio and long‐term mortality after acute myocardial infarction in patients with and without diabetes: A prospective, nationwide, and multicentre registry. Issue 7 (13th July 2022) - Cui, Kongyong; Fu, Rui; Yang, Jingang; Xu, Haiyan; Yin, Dong; Song, Weihua; Wang, Hongjian; Zhu, Chenggang; Feng, Lei; Wang, Zhifang; Wang, Qingsheng; Lu, Ye; et al.
Abstract: Aims: To assess the predictive value of stress hyperglycemia ratio (SHR) for long‐term mortality after acute myocardial infarction (AMI) in patients with and without diabetes. Materials and Methods: We evaluated 6892 patients with AMI from the prospective, nationwide, multicentre China Acute Myocardial Infarction registry, of which 2820 had diabetes, and the remaining 4072 were nondiabetic patients. Patients were divided into high SHR and low SHR groups according to the optimal cutoff values of SHR to predict long‐term mortality for diabetic and nondiabetic patients, respectively. The primary endpoint was all‐cause mortality at 2 years. Results: The optimal cutoff values of SHR for predicting 2‐year mortality were 1.20 and 1.08 for the diabetic and nondiabetic population, respectively. Overall, patients with high SHR were significantly associated with higher all‐cause mortality compared with those with low SHR, in both diabetic patients (18.5% vs. 9.7%; hazard ratio [HR] 2.01, 95% confidence interval 1.63–2.49) and nondiabetic patients (12.0% vs. 6.4%; HR 1.95, 95%CI 1.57–2.41). After the potential confounders were adjusted, high SHR was significantly associated with higher risks of long‐term mortality in both diabetic (adjusted HR 1.73, 95%CI 1.39–2.15) and nondiabetic (adjusted HR 1.63, 95%CI 1.30–2.03) patients. Moreover, adding SHR to the original model led to a slight albeit significant improvement in C‐statistic, net reclassification, and integrated discrimination regardless of diabetic status. Conclusions: This study demonstrated a strong positive association between SHR and long‐term mortality in patients with AMI with and without diabetes, suggesting that SHR should be considered a useful marker for risk stratification in these patients. Trial registration: ClinicalTrials.gov NCT01874691.